Mariana, seus filhos atrapalham: a exaustão e o sofrimento psíquico-social das mães no imaginário brasileiro - Barros, Mariana Della Barba (2024)
This study is motivated by two personal experiences that led to na investigation into the physical, mental, and emotional exhaustion experienced by Brazilian mothers and societal perceptions of this phenomenon. The first experience involved a comment made in my professional environment suggesting that my children were getting in the way of my work as an editor. The second was prompted by observations of the inconsistent and often superficial media coverage of maternal exhaustion, which has been labeled as "maternal burnout." This academic inquiry aims to demonstrate how, within the Brazilian social imaginary, the psychosocial suffering of mothers has been normalized, trivialized, and framed as an individual problem, rather than a collective one. Grounded in feminist epistemologies, this research employs in-depth interviews, media analysis, and a literature review on the construction of motherhood in the West as its methodological framework